Application of wet powder spraying for anode supported solid oxide fuel cell with a perovskite SrTi0.98Nb0.02O3–δ anode. Issue 12 (20th October 2013) - Gdaniec, Pawel; Karczewski, Jakub; Bochentyn, Beata; Gazda, Maria; Molin, Sebastian; Jasinski, Piotr; Krupa, Andrzej; Kusz, Boguslaw
<x xml:space="preserve">Abstract</x> Anode‐supported solid oxide fuel cell with SrTi0.98Nb0.02O3–δanode, yttria‐stabilized zirconia electrolyte and La(Ni0.6Fe0.4)O3±δ cathode has been successfully fabricated and evaluated. Process of anode support fabrication has been presented. Wet powder spraying and high temperature sintering method have been studied and applied to deposit the thin electrolyte layer.In order to improve catalytic properties of the anode, it has been impregnated with Ni. Electrical properties of fuel cells have been measured to determine their performance. The open cell voltage of 1.08 V and maximum power density at the level of 160 mWcm−2 were observed at 800 °C.